Understanding how to recruit and retain participants to a Digital Health Intervention (DHI) for a unique service population - Patel, Shireen (2024)
Background Health anxiety is a debilitating condition prevalent in primary and secondary care settings. Challenges to engaging individuals with health anxiety to cognitive behavioural therapy (CBT) led to the development of a remotely delivered Cognitive Behavioural Therapy (RCBT) randomised controlled trial (RCT) (the “Urgent Care trial”) for the treatment of health anxiety for those accessing unscheduled care services. Whilst an RCT assesses overall effectiveness, the nested piece of qualitative research which forms this thesis is necessary to understand service provider and service user views of trial participation, given that recruitment and retention to trials remains a challenge.